A new empirical equation for termination of twinning in magnesium alloys. (15th July 2016) - Qiao, H.; Wu, P.D.; Guo, X.Q.; Agnew, S.R.
Abstract: Since it is rare that a grain can be fully twinned, an empirical equation has been introduced in the current crystal plasticity models to terminate twinning within that grain. In the present paper, a new empirical equation for describing the termination of twinning in magnesium alloys is developed. The new description introduces only a single parameter, while the widely used empirical equation involves two parameters. It is demonstrated that it is easy to calibrate the single parameter and the proposed empirical equation is able to accurately simulate the experimentally observed rapid hardening associated with the twinning exhaustion. Graphical abstract: